19. \( \frac{9 x^{2}\left(x^{3}-1\right)-4\left(x^{3}-1\right)}{3 x^{2}-x-2} \div \frac{3 x^{2}+3 x+3}{9 x+6} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Mind Expander
Let's simplify the given expression step by step. We start with: \[ \frac{9 x^{2}\left(x^{3}-1\right)-4\left(x^{3}-1\right)}{3 x^{2}-x-2} \div \frac{3 x^{2}+3 x+3}{9 x+6} \] First, we can factor \(x^3 - 1\): \[ x^3 - 1 = (x - 1)(x^2 + x + 1) \] Now, substitute in: \[ = \frac{(9x^2 - 4)(x^3 - 1)}{3 x^{2}-x-2} \div \frac{3 x^{2}+3 x+3}{9 x+6} \] Next, for the term \(3x^2 + 3x + 3\), we can factor out a 3: \[ = \frac{3(x^2 + x + 1)}{3(3x + 2)} = \frac{x^2 + x + 1}{3x + 2} \] Thus, our expression can now be written as: \[ = \frac{(9x^2 - 4)(x^3 - 1)}{3 x^{2}-x-2} \cdot \frac{9x + 6}{x^2 + x + 1} \] Next, factor \(9x^2 - 4\) as a difference of squares: \[ = \frac{(3x - 2)(3x + 2)(x^3 - 1)}{3 x^{2}-x-2} \cdot \frac{9x + 6}{x^2 + x + 1} \] Now, factor \(3x^2 - x - 2\): To factor \(3x^2 - x - 2\), we look for two numbers that multiply to \(-6\) (3 * -2) and add to \(-1\). These numbers are \(-3\) and \(2\). So we write: \[ 3x^2 - 3x + 2x - 2 = (3x + 2)(x - 1) \] Thus, \[ = \frac{(3x - 2)(3x + 2)(x^3 - 1)}{(3x + 2)(x - 1)} \cdot \frac{9x + 6}{x^2 + x + 1} \] Now cancel the \(3x + 2\): \[ = \frac{(3x - 2)(x^3 - 1)}{(x - 1)} \cdot \frac{9x + 6}{x^2 + x + 1} \] Next, simplify \(9x + 6\): \[ = 3(3x + 2) \] Now, combine everything: \[ = \frac{(3x - 2)(x^3 - 1) \cdot 3(3x + 2)}{(x - 1)(x^2 + x + 1)} \] Substituting \(x^3 - 1\) back gives: \[ = \frac{(3x - 2)(x - 1)(x^2 + x + 1) \cdot 3(3x + 2)}{(x - 1)(x^2 + x + 1)} \] Now we cancel \(x -1\) and \(x^2 + x + 1\): \[ = (3x - 2) \cdot 3(3x + 2) \] Finally, our complete simplified expression is: \[ = 3(3x - 2)(3x + 2) = 3(9x^2 - 4) = 27x^2 - 12 \] Thus, the final answer is: \[ \boxed{27x^2 - 12} \]